A study on the level of terrestrial gamma and gross alpha activity in Gulf of Mannar, South coast of India, Tamil Nadu - Raju Krishnamoorthy; O Basith; M Jamal Mohamed Jaffer (Radiation Protection and Environment, 2022)
This study presents the results of outdoor ambient gamma and gross alpha activity of Gulf of Mannar, and these measurements were carried out using Scintillation Counter (UR-705). Results showed that the terrestrial Gamma radiation levels of the Gulf of Mannar ranged from 4.10 μR/h to 76.33 μR/h. The Gross alpha radioactivity levels of the Gulf of Mannar ranged between 3.67 Bq/kg and 51.34 Bq/kg. The calculated ambient gamma and gross alpha activity were found to be lower than the world average. Gamma absorbed dose rates in air outdoors were calculated to be in the range between 35.67 nGy/h and 664.07 nGy/h with an arithmetic mean of 98.98 ± 20.54 nGy/h. This value is lower than the population-weighted world-averaged of 60 nGy/h. Inhabitants of Northern Gulf of Mannar are subjected to external gamma Annual dose exposure ranging between 0.30 and 5.65 mGy/y with an arithmetic mean of 0.84 ± 0.17 mGy/y.